Arthroscopic Superior Capsular Reconstruction With Mesh Augmentation for the Treatment of Irreparable Rotator Cuff Tears: A Comparative Study of Surgical Outcomes. Issue 13 (November 2020) - Kholinne, Erica; Kwak, Jae-Man; Kim, Hyojune; Koh, Kyoung Hwan; Jeon, In-Ho
Background: Arthroscopic superior capsular reconstruction (ASCR) is an alternative to open surgery for irreparable chronic rotator cuff tears (RCTs). This approach can provide static restraint while avoiding upward migration of the humeral head. However, graft tears and their effect on clinical outcomes after ASCR remain a debated topic. Purpose: To evaluate the clinical outcomes of ASCR with mesh augmentation for the treatment of irreparable RCTs. Study Design: Cohort study; Level of evidence, 3. Methods: The data of 72 patients with irreparable RCTs who underwent ASCR between 2013 and 2018 were retrospectively evaluated. Among them, 64 patients who met the inclusion and exclusion criteria were enrolled in this study. Fascia lata grafts augmented with a polypropylene mesh were used for 30 patients (mesh group), and grafts without mesh augmentation were used for 34 patients (control group). Clinical outcomes were evaluated using range of motion, the American Shoulder and Elbow Surgeons (ASES) questionnaire, and visual analog scale for pain. Radiological outcomes were evaluated according to acromiohumeral distance and stage of rotator cuff arthropathy. The status of fatty infiltration and graft integrity was evaluated using magnetic resonance imaging. Outcomes were assessed preoperatively and at the final follow-up. Results: Both groups showed improvement in clinical and radiological outcomes at the final follow-up. The mesh group demonstrated a larger improvement in ASES score (mean ± SD, 29.1 ± 15.8) than the control group (18.1 ± 15.9) ( P = .006). The mean improvement in active forward flexion was significantly higher in mesh group (40°± 26°) than in control group (28°± 23°) ( P = .003). The mean improvement in active external rotation was also significantly higher in the mesh group (11°± 5°) than in the control group (6°± 3°) ( P = .004). Graft healing rate was significantly higher in the mesh group (83.3%) than in the control group (58.8%) ( P = .039), and acromiohumeral distance was significantly greater in the mesh group (9.1 ± 2.4 mm) than in the control group (6.3 ± 1.8 mm) at the final follow-up ( P = .001). Subgroup analysis revealed that patients with graft failure generally showed progression of fatty infiltration without improvement in the stage of rotator cuff arthropathy. Patients with intact grafts demonstrated a more substantial improvement in functional outcomes (ASES score and forward flexion motion). Conclusion: ASCR with mesh augmentation reduced graft failure rate to restore superior shoulder joint stability.